Rare bird documentation form for Northern Goshawk at Red Rock Reservoir, 1981 - Thornburg, Robert E.et al (1981)
Rare bird documentation form for a Northern Goshawk at Red Rock Reservoir in Marion County, IA on February 6, 1981. Epson - sheet feed